RETRACTED: Association of Body Mass Index (BMI) and Severity of COVID- 19: A Multicentric Study from Maharashtra, India - M., Talapalliwar; P., Menon; W., Padole; S., Thakur; M., Phadke; S., Saunik (International Journal of Nutrition, 2025)
This article has been retracted on 30 August 2025. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2379-7835.ijn-25-5842) Objective The COVID-19 pandemic has led to the global research efforts to identify the risk factors which would lead to severe COVID-19 disease. This study aimed to investigate the relationship between body mass index (BMI) and severity of coronavirus disease 2019 (COVID-19). Methods A total of 2820 patients hospitalized with COVID-19 disease in nine Government Medical Colleges, COVID hospitals or COVID care centers of Maharashtra were included in the study. Interviews were conducted on the telephone and counselling was done. Results Among 2820, 2442 (86.60%) were asymptomatic or had a mild or moderate illness. More than half of the total COVID- 19 positive cases, 1591 (56.41%), were in the normal BMI range, and of these only 183 (11.50%) had severe COVID-19 disease. On the other hand, 647 (22.94%) patients were overweight and 106 (16.38%) had Severe COVID- 19 disease. Similarly, the patients who were obese, 363 (84.03%) were asymptomatic and 69 (15.97%) had severe COVID- 19 disease. Odds ratio for this association was found as 1.5, which indicates that patients who were obese (BMI ≥ 27.5) had one and half times increased odds of progression to severity as compared to patients having normal BMI. This association was found to be statistically significant (p- value < 0.05). Conclusion Our findings highlight the significant role of BMI in clinical progression of COVID-19 disease. Patients with underweight and obesity experienced more severe outcomes than those of normal weight when being hospitalized with COVID-19 disease.
Keywords: BMI; COVID- 19; Outcome; Obesity